Optimizing Dental Implant Outcomes: A Comprehensive Approach to Preventing and Managing Peri-Implantitis - Malek A. Abdulmatlob; Anas R. Elharathi; Abdalmawla Alhussin Ali Ali; Khalid M. Gondi (Sirte Journal of Medical Sciences, 2024)
Background: Peri-implantitis, a progressive inflammatory condition affecting dental implants, poses a significant threat to the long-term success of implant therapy. This study aimed to develop a comprehensive protocol for the prevention and management of peri-implantitis, integrating various preventive and therapeutic interventions. Methods: A multi-center, prospective, randomized controlled trial was conducted, involving 492 participants randomly assigned to five study groups: control, preventive intervention 1 (surface modification), preventive intervention 2 (patient education), therapeutic intervention 1 (regenerative techniques), and therapeutic intervention 2 (adjunctive antimicrobial therapies). Clinical assessments, including periodontal parameters, marginal bone levels, and patient-reported outcomes, were evaluated over a 5-year follow-up period. Results: All intervention groups showed significantly greater improvements in periodontal parameters, marginal bone levels, and patient-reported outcomes compared to the control group (p < 0.05). The therapeutic intervention group 1 (regenerative techniques) demonstrated the most favorable outcomes, with the greatest reductions in probing depth, clinical attachment level, bleeding on probing, and plaque index, as well as the smallest marginal bone loss and highest implant survival rate (94.2%). Participants in this group also reported the highest oral health-related quality of life, lowest pain and discomfort levels, and highest satisfaction with treatment outcomes. Conclusion: The findings highlight the efficacy of various preventive and therapeutic interventions in optimizing dental implant outcomes and improving patient quality of life. The multidisciplinary approach adopted in this study contributed to the development of a comprehensive protocol for the prevention and management of peri-implantitis, integrating cutting-edge research and evidence-based practices